Timing luck ebook - Duggan, Gerry (Image Comics, 2024)
GERRY DUGGAN takes you along his journey through comic books and Hollywood.  The book contains hundreds of photos over two decades in writing rooms, green rooms, and city streets around the world. Each photo tells a story, and collectively the book tells his. TIMING/LUCK is a mash-up of dark streets, bright minds, and green rooms featuring your favorite comics creators, comedians, writers, and filmmakers.